Reflections on the Phenomenological Description of the Experience of a Teacher in a Colombian Public School - Castrillón, Maricela Correa (Journal of Ecohumanism, 2026)
This paper is the result of a research process focused on studying the experience of teachers in Colombian public schools. It argues that, based on a phenomenological description, it is possible to challenge the instrumentalist perspective that permeates this experience. Among the various approaches to phenomenology, I opt for Michel Henry’s (2015) proposal, which explores the deepest layers of the unfolding of experience and describes affectivity as the ultimate foundation of meaning-making. Reclaiming Henry’s perspective entails a particular approach to the study of experience, where, in addition to transcendence, I attend to the ontological sphere of immanence. It is the broadening of meaning with respect to the ontological realities in which life finds its fulfillment that allows us to consider reframing the lived experience in school, as well as to raise questions about how different concepts related to it are understood. In particular, this article reflects on the concepts of knowledge and education.